Komitmen Kerja Pegawai di Kantor Camat Kecamatan Lemito Kabupaten Pohuwato - Adisty Zahrawanty Laisa; Yanti Aneta; Muchtar Ahmad (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This research aims to provide a detailed description and comprehensive understanding of employee work commitment at the Lemito District Office, Pohuwato Regency, and its impact on employee performance. This research is motivated by various problems related to employee performance that are still frequently encountered, including low work discipline, declining work motivation, a lack of a sense of responsibility, and limited employee awareness of their contributions to achieving organizational goals. This research employs a qualitative, descriptive research design. This approach was chosen to obtain an in-depth understanding of the phenomenon of employee work commitment through direct observation, interviews, and document analysis. Research respondents were selected purposively, including the regent, the district secretary, department heads, and staff. Data collection techniques included in-depth interviews, observation, and document analysis. Based on the research findings, it can be concluded that employee work commitment at the Lemito District Office is formed through three dimensions: Affective commitment, Continuance commitment, and normative commitment. Affective commitment is evident in employees' emotional attachment to the organization; however, there is still room for improvement. Continuance commitment arises from the need for job stability and the benefits derived from the employment. Meanwhile, normative commitment is reflected in employees' moral awareness in carrying out their duties and responsibilities as government officials. Overall, employee work commitment is fairly good, but not yet optimal in supporting improved performance and quality of public services. Therefore, efforts to enhance commitment through motivation, recognition, and continuous development are necessary to maximize employee performance.